2021
DOI: 10.14719/pst.2021.8.2.1113
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, alpha glucosidase and antibacterial evaluation of Syzygium mytifolium (Roxb.) Walp.

Abstract: Medicinal plants have been the major source of combating and treating infectious diseases and health disorders throughout the ages. To explore new sources of inexpensive and safe antioxidants and antibiotics. The antioxidant and antibacterial potential of different extracts Syzygium mytifolium (Roxb.) Walp. were evaluated through 1,1-Diphenyl-2-Picryl Hydrazyl (DPPH), ferric reducing antioxidant power (FRAP), ?-glucosidase inhibition, disk diffusion and agar well methods. The leaves, bark, root and whole plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Generally, the leaves of the Myrtaceae are in the opposite direction, internal phloem, evergreen and woody and abundance of oil glands in most of the members (38). The members are bisexual with polystemonous, fully inferior or partial inferior ovaries mostly with nectariferous hypanthium and actinomorphic flower (36).…”
Section: Taxonomic History Of Myrtaceaementioning
confidence: 99%
See 4 more Smart Citations
“…Generally, the leaves of the Myrtaceae are in the opposite direction, internal phloem, evergreen and woody and abundance of oil glands in most of the members (38). The members are bisexual with polystemonous, fully inferior or partial inferior ovaries mostly with nectariferous hypanthium and actinomorphic flower (36).…”
Section: Taxonomic History Of Myrtaceaementioning
confidence: 99%
“…History has shown that these species originated from South Asia countries like Nepal, Sri Lanka, Pakistan and India (38,43). Though they are distributed all over the world, they are mostly found in tropical and subtropical regions (43).…”
Section: Evolution and Ecological Distributionmentioning
confidence: 99%
See 3 more Smart Citations